(3NWGHGJ GdCYeGd GdYedjI (B/s - (3Rhjd, eMehO Cejfs ((3GdEScfOQjI(B: s (3OGQ GdhaGA dOfjG GdWHGYI hGdfTQ(B, s, 2000)
(3cJGHI QSGdI GdCYeGd,NUGFU QSGdI GdCYeGd GdLjOI hYfhfI GdeXGQja,GdHQjO GdhGQO hGdHQjO GdUGOQ, GdeQGSdGJ GdOGNdjI,GdNUe,GdahGJjQ,GdNWGHGJ GdeQabIs
Keywords: (3EOGQIs; (3cJGHI QSGdI GdCYeGd(B((3cJGHI GdJbGQjQ(B)s